Cordel on Facebook: support capabilities in the case of the string “Política x Amizade” (RuMoRes, 2016)
This study analyzes the potential that Facebook offers to Cordel poetry from the video “Política x Amizade” by Braulio Bessa. It presents an analysis of the political ideas’ debate in social networks in the context of the presidential Brazilian elections in 2014, and the implications of its dissemination on Facebook. Our goal is to relate the content of the verses that discuss the polarization and conflicts on the network to the potential that Facebook offers to Cordel poetry, which leads us to realize that the digital platform and the content are directly linked to the production of meaning.